Primary-Secondary Wavelength Spectrophotometry to Improve the Determination of Trace Amounts of Nickel in Waste Water - Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
In ammoniacal solution of nickel, in presence of iodine the conventional reaction of nickel (Ni2+) with diacetyldioxime to form red complex has been applied for the improvement of the determination of trace amounts of nickel in water and waste water by the updated method named primary–secondary wavelengths spectrophotometry (PSWS). The results show that the analytical precision and accuracy were increased and gave the higher determination sensitivity than the ordinary spectrophotometry. The relative standard deviations were less than 1.3% and the recovery rate of Ni between 96 and 102%.